Treće oči, ili o granicama vizualnosti - Užarević, Josip (Array, 2003)
The category of visuality is the dominant factor of human culture in the 20th century, when the boundary of the visible expends with the emergence of new optical machines, media, and arts. The boundaries of visuality are defined as the feature of vision which itself remains invisible, and which becomes intelligible only when the visual (eye, sight) meets itself (for example in Ahmatova or Mandel'štam - objectification of self in the mirror). It is also possible to find the border of visuality in the process of transformation of images into symbols, as it happens in a letter (writing).